Tinjauan Good Governance atas Aplikasi JakLapor - Sulaiman, Ariq Nabil; Rizkika, Salsa (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to analyze the implementation of good governance principles in the context of the public service complaint application in the DKI Jakarta Province: JakLapor. JakLapor is designed to respond to public issue complaints in a centralized manner, making principles of good governance such as accountability, community participation, transparency, equality, legal foundation, strategic objectives, responsiveness, consensus orientation, effectiveness, and efficiency crucial to fulfill. This study employs a qualitative approach to provide a in-depth understanding of the application of Good Governance principles in the procurement and implementation of public complaint services through JakLapor in the DKI Jakarta Province. Data collection techniques involve literature studies as secondary data. Data and information are gathered from credible sources, including books, journals, articles, and documents related to the research topic. Data analysis is conducted using illustrative techniques, matching patterns based on the principles of good governance outlined by the United Nations Development Programme. The research findings indicate that in the implementation of JakLapor, good governance principles have been applied, but the features still face some challenges and shortcomings in achieving these principles.